EDUCATION AND CREATIVITY: SAFE USE OF SYNTHETIC DYES IN TIE-DYE BATIK FOR STUDENTS: EDUKASI DAN KREATIVITAS: PENGGUNAAN PEWARNA SINTETIS BATIK CELUP YANG AMAN PADA SISWA - Arshy Prodyanatasari; Mely Purnadianti; Jerhi Wahyu Fernanda (Darmabakti Cendekia: Journal of Community Service and Engagements, 2026)
Background: A community service initiative was carried out at SDN Bujel 1, Kediri, to address primary education challenges that require a holistic approach to character, creativity, and culture. Batik, a UNESCO-recognized heritage, is often perceived as complicated and risky for children. This initiative introduces a safe, child-friendly tie-dye technique that integrates culture, safety, and the local wisdom of Kediri. Objective: To conduct a safe tie-dye batik workshop aimed at boosting elementary students' creativity, cultural appreciation, and safety awareness, while also empowering teachers through an ongoing mentoring model. Method: A practical workshop was held at SDN Bujel 1, Kediri, in May 2025, with 25 fifth-grade students participating. The methods employed included learning by doing, close mentoring, and assessment of the process, results, and effects via a mini exhibition, surveys, and a post-test. Results: Overall, 95% of students took an active part, achieving an average artwork score of 86.5. Their grasp of safe dyes and the batik process was 88%, while satisfaction averaged 4.6 out of 5. Beyond technical skills, the activity also boosted participants' self-confidence, curiosity, and appreciation for culture. Conclusion: This tie-dye batik workshop was shown to be an effective, holistic, and safe model for arts and cultural education at the elementary school level. With collaboration and teacher empowerment, the model is sustainable and suitable for integration into the school curriculum.